ALENDRONATE-INDUCED RESPIRATORY DISTRESS - M, PRAVALIKA; V, SRIVANI; PAMU, SAGAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Respiratory distress is a rare adverse effect of alendronate that is typically associated with severe dyspnoea and wheezing and typically requires hospitalization. The patient with a history of dyspnoea and wheezing during the strenuous workload was treated promptly with alendronate for newly diagnosed osteoporosis. After 2 days, respiratory distress complications were restarted and we accurately reported the patient with basophilia, elevated immunoglobulin E (with a blood test), and allergic bronchopulmonary aspergillosis (with computed tomography scan image). The prospective patient was adequately understood as alendronate-induced respiratory distress with an unfortunate rechallenge method. Although there is no direct causal relationship from this adverse case report, the possible mechanism has discussed typically based on peer-reviewed literature.